The Relationship Between Symmetrical Internal Communication, Employer Branding, Organizational Identification and Turnover Intention - Kağan Cenk Mızrak; Funda Yalım (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
It is accepted by both employers and academic circles that employees in the modern management approach are effective in the success of the organizations they work for. Employees also play a role in organizations creating competitive advantage. Employer branding practices in an organization at the point of creating a strong employer brand not only offer an attractive value package for qualified employees, but also ensure that qualified employees, who are an important competitive advantage for the organization, continue to work in the organization. Therefore, examining the factors associated with employer branding emerges as an issue that needs to be carefully evaluated for the sustainable success of organizations. The main purpose of this research is to examine the relationship between employer branding, symmetrical internal communication, organizational identification and turnover intention. 413 people working in Istanbul-based Turkish airline companies constitute the sample of the research. Quantitative research technique was used in the study and descriptive and relational scanning design was preferred. As a result of the research, a significant and positive relationship was found between symmetrical internal communication and employer branding, and it was determined that organizational identification mediated the relationship between employer branding and turnover intention.